1992
DOI: 10.1016/0014-5793(92)80128-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of the fabD gene encoding malonyl coenzyme A‐acyl carrier protein transacylase of Escherichia coli

Abstract: We report the cloning and nucleotide sequence of the gene encoding malonyl coenzyme A‐acyl carrier protein transacylase of Escherichia coli, Malonyl transacylase has been overexpressed 155‐fold compared to a wild‐type strain, Overexpression of this enzyme alters the fatty acid composition of a wild‐type E. coli strain; increased amounts of cis‐vaccenate are incorporated into the membrane phospholipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Hence, the evolutionary origin for MdcH may be a gene operating in the synthesis of polyacetate compounds. Recently, the fabD gene of E. coli has been cloned [26,27] and the structure of its gene product determined [28]. The active site of the enzyme is related to a/b hydrolases where SerHis and Asp/Glu operate together as a charge relay system.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the evolutionary origin for MdcH may be a gene operating in the synthesis of polyacetate compounds. Recently, the fabD gene of E. coli has been cloned [26,27] and the structure of its gene product determined [28]. The active site of the enzyme is related to a/b hydrolases where SerHis and Asp/Glu operate together as a charge relay system.…”
Section: Discussionmentioning
confidence: 99%
“…fatty acid or polyketide synthases has demonstrated that a serine, such as Ser-92 in the E. coli FabD protein (16,22,25), is the active nucleophilic residue of these enzymes. During its transfer from malonyl-CoA to ACP, the malonyl moiety is transiently attached to this serine to form a stable malonyl-serine enzyme intermediate (26).…”
Section: Construction and Activity Of Various Mtfabd Mutant Proteins-mentioning
confidence: 99%
“…Moreover, acetyl-CoA:ACP and malonyl-CoA:ACP AT activities distinct from the E. coli FabB (KS I) protein (Fig. 3) are reportedly involved in E. coli fatty acid biosynthesis (18)(19)(20)27), and the E. coli FabH (KS III) protein even lacks the conserved GH SXG motif yet exhibits both acetyl-CoA:ACP acetyltransferase…”
Section: Fig 2 Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophomentioning
confidence: 99%